2005
DOI: 10.1016/j.jpainsymman.2005.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Pilot of a Pathway to Improve the Care of Imminently Dying Oncology Inpatients in a Veterans Affairs Medical Center

Abstract: We report on the implementation of a previously developed clinical pathway for terminally ill patients, Palliative Care for Advanced Disease (PCAD), on a Veterans Administration (VA) acute care oncology unit, comparing processes of care and outcomes for patients on and off the pathway. The PCAD pathway is designed to identify imminently dying patients, review care goals, respect patients' wishes, assess and manage symptoms, address spirituality, and support family members. Retrospective chart reviews from 15 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…Patients on such pathways are reviewed regularly, medication is prescribed in line with good practice guidelines, and the holistic needs of the patient and family are addressed. Entry onto an end of life care pathway depends on clinicians being alert to the possibility that the patient may be dying and is based on clinical judgment after careful assessment 20. …”
mentioning
confidence: 99%
“…Patients on such pathways are reviewed regularly, medication is prescribed in line with good practice guidelines, and the holistic needs of the patient and family are addressed. Entry onto an end of life care pathway depends on clinicians being alert to the possibility that the patient may be dying and is based on clinical judgment after careful assessment 20. …”
mentioning
confidence: 99%
“…A trial implementation of this system in a teaching hospital showed improvements in symptom assessment and management, higher likelihood of DNR orders, and decreased number of consultations [98]. This clinical pathway has been piloted on an oncology unit in a VA hospital with findings of more frequent care plans and symptom assessment and documentation [99].…”
mentioning
confidence: 99%
“…Care pathways were proposed in the National Institute for Health and Clinical Excellence Guidance on Supportive and Palliative Care [55] as a possible means to improve end-of-life care, although needing more evaluation. In the USA, three before-and-after studies of care pathways suggested that there was a reduction in the number of therapies ordered, although outcomes were not studied [56-58]. Studies on the LCP in the UK found similar data using documentation and staff appraisals [59-61], and caregiver reports [60].…”
Section: Discussionmentioning
confidence: 99%